2015
DOI: 10.1093/rheumatology/kev123
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous neridronate in the treatment of acute painful knee osteoarthritis: a randomized controlled study

Abstract: ClinicalTrials.gov (http://clinicaltrials.gov), NCT01803360.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 37 publications
2
33
0
2
Order By: Relevance
“…We tested whether osteoclast enzymes released during bone resorption, cath-K and TRAcP5b 38,39 , could serve as markers of subchondral osteoclast activity. Our data, linking osteoclast activity, as reflected by serum TRAcP5b, with OA pain provide a clear biological mechanism that could explain the reported analgesic benefit of anti-resorptives such as bisphosphonates in human 40,41 and rodent OA 7 . We also observed at baseline, an association of serum TRAcP5b with subchondral bone sclerosis as well as with WOMAC pain scores, further suggesting a link between subchondral bone remodelling and pain generation in OA.…”
Section: Discussionmentioning
confidence: 63%
“…We tested whether osteoclast enzymes released during bone resorption, cath-K and TRAcP5b 38,39 , could serve as markers of subchondral osteoclast activity. Our data, linking osteoclast activity, as reflected by serum TRAcP5b, with OA pain provide a clear biological mechanism that could explain the reported analgesic benefit of anti-resorptives such as bisphosphonates in human 40,41 and rodent OA 7 . We also observed at baseline, an association of serum TRAcP5b with subchondral bone sclerosis as well as with WOMAC pain scores, further suggesting a link between subchondral bone remodelling and pain generation in OA.…”
Section: Discussionmentioning
confidence: 63%
“…According to the results of a randomized, double-blind, placebo-controlled study, daily 6 Clinical Medicine Insights: Therapeutics 100 mg intravenous neridronate injections for 10 days significantly reduced pain and improved the quality of life of patients with acute pain caused by knee OA compared with the placebo. Furthermore, the neridronate group exhibited a significant decrease in bone marrow lesions evaluated by MRI, 49 suggesting a possible structural effect based on the hypothesis that altered bone metabolism plays a role in the pathogenesis of OA. [50][51][52][53] …”
Section: Osteoarthritismentioning
confidence: 94%
“…A randomized controlled trial of vitamin D supplement vs placebo in more than 400 patients with KOA did not show significant differences in either MRI-measured tibial cartilage volume change or WOMAC knee pain change over 2 years 59 . In contrast a study of intravenous Neridronate was found to significantly improve clinical symptoms compared to placebo and to reduce BMLs after 2 and 4 months in patients with symptomatic KOA 60 . Intraarticular injection of Sprifermin was reported to increase cartilage thickness or reduce cartilage loss in KOA 61 and intraarticular allogeneic bone marrow mesenchymal stem cell therapy showed indication of clinical efficacy and improved cartilage T2map status compared to intraarticular hyaluronic acid 62 .…”
Section: Treatment Responsementioning
confidence: 78%